The Effect of Using Quiet Book Media on Improving Personal Hygiene Skills in Children with Intellectual Disabilities - Mafitroh, Uyun; Hardini, Deisy Sri (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Children with intellectual disabilities experience cognitive limitations that affect their ability to perform self-care tasks, including maintaining personal hygiene. This study aims to analyze the effect of using quiet book media on improving personal hygiene skills among children with intellectual disabilities at SLB C and C1 Yakult Purwokerto. A pre-experimental design with a one-group pretest-posttest approach and a quantitative method was used. Data were analyzed using the Wilcoxon Signed Rank Test. A total of 30 students were selected through total sampling. Data were collected using questionnaires and observation sheets. The results showed a significant improvement in personal hygiene skills after the intervention, with a p-value of <0.001. The quiet book media proved effective in enhancing children's behavioral skills in self-care. Therefore, this media can serve as a practical alternative learning tool to support the independence of children with intellectual disabilities, particularly in fulfilling personal care needs.